A Literature Review on Learning Innovations in Atomic Structure Materials - Fachri Hakim; Evril Suherni Dewi; Adilah Irfah; Hafidhoh Kamalatul Iffah (Universitas Negeri Gorontalo, 2026)
The issue lies in the difficulty students face in understanding abstract chemistry concepts, particularly atomic structure. Traditional teacher-centered approaches, with limited use of technology and innovation, lead to low student motivation, reduced interest in learning, and suboptimal comprehension of key concepts.This study aims to provide an overview of new learning strategies in the topic of atomic structure in chemistry learning. The research method used is a study literature review through a website using the google scholar database and the Publish or Perish application. This research technique uses qualitative analysis with a focus on data obtained from journals regarding learning innovations presented in the form of tables and narratives. The results of the study show that journal publications on chemistry learning innovations tend to increase, especially in 2019. The level of accreditation varies, with most indexed at sinta levels 3 and 4. The types of learning innovations found include learning media, learning models and learning methods. Innovation in learning media is the main focus, followed by learning models and methods. This review reveals that the most effective chemistry learning innovations involve learning media such as digital modules, interactive multimedia, and virtual laboratories, supported by problem-based and inquiry-based learning models, which enhance interactivity, clarity, efficiency, and student learning outcomes while promoting sustainability in chemistry education.